Case Report: Hemoglobin titusville: a specific case of cyanosis - Zhang, Meng; Wang, Kai; Xu, Xinyi; Ji, Wei; Guo, Ying; Gao, Wei; Liu, Tingliang (Frontiers in Cardiovascular Medicine, 2025)
Hemoglobin Titusville is a rare low-oxygen-affinity hemoglobinopathy characterized by normal arterial partial pressure of oxygen but low oxygen saturation. In this study, we describe a case of hemoglobinopathy presenting as cyanosis. A 12-year-old female patient was admitted to the hospital with cyanosis and 87% blood oxygen saturation. Overall, the patient was healthy and preserved exercise tolerance. Upon admission, her arterial partial pressure of oxygen was 121 mmHg, and her blood oxygen saturation was 89.7%. First, the common causes were excluded, after which cardiovascular catheterization was performed. This detected no shunt between the systemic and pulmonary circulation. Finally, whole-exon sequencing confirmed a heterozygous mutation of the HBA1 gene (g.227115G>A). In this study, we review the entire course of this case, providing scientific insight into this disease and a differential diagnosis of cyanosis.